2020
DOI: 10.1016/j.jobcr.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative method to determine osteogenic differentiation aptness of scaffold

Abstract: Osteogenic differentiation of Mesenchymal stem cells (MSCs) on scaffold is crucial for bone tissue engineering. Alkaline phosphatase (ALP) assay is an important method of assessing osteogenesis. Here, a very simple and innovative procedure is being described for quantification of osteogenic differentiation of MSCs in presence of scaffold using ALP assay. Different concentrations of the scaffold particles with the same number of MSCs were assayed for alkaline phosphatase activity using p-NPP as substrate for AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…As an early indicator of osteoblast differentiation, ALP regulates the extracellular matrix mineralization. , In this work, the ALP activity of MC3T3-E1 cells was evaluated after cultivation for 7 days. The results showed that the ALP activity on the Ti2448-PDA-ECM scaffolds was noticeably higher than that from the Ti2448 scaffolds (Figure c and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…As an early indicator of osteoblast differentiation, ALP regulates the extracellular matrix mineralization. , In this work, the ALP activity of MC3T3-E1 cells was evaluated after cultivation for 7 days. The results showed that the ALP activity on the Ti2448-PDA-ECM scaffolds was noticeably higher than that from the Ti2448 scaffolds (Figure c and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…To gain further insight into the tissue-specificity of ECM, relative mRNA expression of ALP and ACAN was investigated. ALP is recognized as an early marker of osteoblast differentiation as it is a by-product of osteoblast activity, thereby suggesting a correlation between increased expression and active bone formation [ 36 ]. ACAN is recognized as a hallmark of articular chondrocytes as its covalently attached sulfated glycosaminoglycan [ 10 ] chains exert water-attracting characteristics and generate a fixed negative charge of cartilage [ 8 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary marker of osteoblasts, alkaline phosphatase, is a membrane enzyme that hydrolyzes phosphate ions, allowing the formation of hydroxyapatite crystals and stimulating mineralization. ALP plays a crucial role in bone regeneration and differentiation [ 110 ]. Compared to pure gelatin scaffold, Li-doped bioactive glass, PRGF, and a combination group showed a substantial increase in ALP activity with increasing culture time.…”
Section: Discussionmentioning
confidence: 99%